SEMANTIC ANALYSIS OF LEXICAL UNITS AND THE ISSUE OF ADEQUACY IN TRANSLATION (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This study examines the semantic analysis of lexical units and the issue of adequacy in translation within modern linguistics. It focuses on how meaning is conveyed across languages and the challenges translators face in preserving semantic accuracy. The research highlights the role of lexical-semantic transformations, contextual interpretation, and cultural factors in achieving adequate translation. By analyzing theoretical approaches and practical examples, the study identifies effective strategies for maintaining equivalence between source and target texts, ensuring clarity, accuracy, and communicative effectiveness in translation processes.